111k views
4 votes
2(x - 4) + 2x = -6x – 2

User EKS
by
4.7k points

2 Answers

5 votes

Answer:

x= 0.6

Explanation:

User Arth Du
by
4.9k points
2 votes

Answer:


x = (3)/(5)

Explanation:

  1. Apply the distributed property to 2(x - 4). It should now look like this: 2x - 8
  2. Plug 2x - 8 in: 2x - 8 + 2x = -6x - 2
  3. Combine like terms on the left side, so it now looks like this: 4x - 8 = -6x - 2
  4. Combine like terms even further: 4x - -6x = 8 - 2
  5. Simplify: 4x + 6x = 6
  6. Start adding, so it now looks like this: 10x = 6
  7. Divide each side by 10 to cancel out the 10 next to x. It should now look like this: x = 3/5

I hope this helps!

User FedG
by
5.0k points